Meningkatkan Kecerdasan Finansial Anak Usia Dini Melalui Permaianan Monopoli Modifikasi - Aas Hasanah Aas (Jurnal Edukasi Sebelas April, 2020)
The purpose of this study is to increase learning activities and improve the financial intelligence of children aged 5-6 years. The research method used is classroom action research with research design according to the Kemmis & Taggart model with a spiral model system with research stages planning, implementing, observing, reflecting. The formulation of the problem in this study is whether the modified monopoly game can increase children's learning activities, and whether the modified monopoly game can improve financial intelligence?. After two cycles of action, the results in the first cycle showed the overall result, namely 50% or with an average score of 2.6 in the Develop as Expected category and in the second cycle, the overall result is 91.7% or with an average score of 3.3 in the Very well developed category. Financial intelligence in the first cycle showed an overall result of 41.7% or with an average score of 2.7 in the Develop as Expected category, and the second cycle, the overall result was 91.7% or with an average of 3.2 in the Very well Developed category. Thus, it was concluded that after two actions were carried out through the application of the monopoly game, the modification of learning activities and the financial intelligence of early childhood could be improved.